N-body problems and models - Greenspan, Donald (World Scientific, 2004)
The study and application of N-body problems has had animportant role in the history of mathematics. In recent years, theavailability of modern computer technology has added to theirsignificance, since computers can now be used to model material bodiesas atomic and molecular configurations, i.e. as N-bodyconfigurations.